Tracheobronchopathia osteochondroplastica limited to the trachea: a case report and rewiew of literature - Kargı, Ahmet Bülent; Atlı, Eray; Kılıç, Bilge; Bilgin, Pelin (The European Research Journal, 2023)
Tracheobronchopathia Osteochondroplastica (TO) is a rare and benign disease with a progressive course. Its clinical manifestation is observed on computed tomography by the presence of diffuse osteocartilage submucosal nodules invading the lumen of the trachea and usually the main bronchi. Bronchoscopic evaluation is necessary for differential diagnosis. Standard treatment has not been determined as few patients have been reported in the literature. A 58-year-old male patient was admitted to our hospital with complaints of cough and dyspnea increasing with exertion. A fiberoptic bronchoscopy demonstrated many protruding lesions along the trachea with no involvement of the bronchial system. The patient was stable at a two-year follow-up.